United States, messenger seaplane on beach in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
View from beach of Arctic Messenger Seaplane docked on coast. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3